Effectiveness of Expiratory Muscle Strength Training on Dysphagia Risk in Pre-Frail Elderly - Ida Ayu Putu Diana Janaki Sari; Erna Setiawati; Lisa Nurhasanah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Pre-frail dan frail elderly are susceptible to dysphagia. Dysphagia leads to vulnerability to aspiration pneumonia, undernutrition, and dehydration, which negatively affect physical condition and quality of life. Expiratory muscle strength training (EMST) is an intervention for dysphagia. However, the effects of EMST on pre-frail elderly are still unclear. This study aimed to investigate effectiveness of expiratory muscle training on dysphagia risk of pre-frail elderly. The study design was a randomized clinical trial. Twenty-four pre-frail elderly at Rindang Asih I and II Elderly Social Service Institution randomly assigned into experimental group (n=12) or control group (n=12). The experimental group received expiratory muscle training using PEP Threshold® device 5 times per week for 6 weeks. Both of group also received typical multicomponent exercise for elderly 3 times per week for 6 weeks. Outcome measure was risk of dysphagia assessed using Swallowing Disturbance Questionnaire (SDQ). The intra-group analysis showed significant differences pre- and post-intervention in experimental group but not in control group (p<0,001 and p=0,107, respectively). Inter-group analysis showed significant differences between experimental and control group post-intervention (p<0,001). This finding indicate that expiratory muscle training effective on reducing dysphagia risk in pre-frail elderly.